131k views
1 vote
Sinxcos y = 1/3(sin(x + y) + sin(x - y)) TRUE OR FALSE

User Shachaf
by
6.1k points

1 Answer

3 votes

Answer:

Explanation:

false (counter-example) : put x = π/6 and y = π/3

calculate 1) sinxcos y you have : (sinπ/6)(cosπ/3) = (1/2)(1/2) = 1/4

2) 1/3(sin(x + y) + sin(x - y))

x+y = π/6 +π/3 = π/2

x - y = π/6 - π/3 = - π/6

so : 1/3(sin( π/2) + sin(- π/6)) = 1/3 ( 1 -1/2)= 1/6 because : sin( π/2) = 1

sin(- π/6) = - sin( π/6) = - 1/2

but :1/4 ≠ 1/6

User Lucuma
by
6.3k points